2019
DOI: 10.1215/00182702-7551912
|View full text |Cite
|
Sign up to set email alerts
|

Reacting to the Lucas Critique

Abstract: and two anonymous referees for their valuable comments on preliminary versions of this paper. The usual caveat applies. diversity, the Keynesians' reactions were characterized by their common questioning of the empirical and practical relevance of the Lucas Critique. 5 Indeed, these Keynesians took the Critique to have to pass an empirical test. An older generation a priori denied the Critique but put the burden of the empirical proof on new classical macroeconomists. Among those, we discuss the arguments and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Consider the collection titled Rational Expectations and Econometric Practice (Lucas and Sargent 1981). Goutsmedt et al (2019) argue that many Keynesians criticised Lucas (1976) on empirical grounds. 14 However, others concluded that only very limited conclusions could be derived from disequilibrium methods, and that the approach was of little value (see Laroque and Salanie 1995).…”
Section: On Theoretical Rigourmentioning
confidence: 99%
“…Consider the collection titled Rational Expectations and Econometric Practice (Lucas and Sargent 1981). Goutsmedt et al (2019) argue that many Keynesians criticised Lucas (1976) on empirical grounds. 14 However, others concluded that only very limited conclusions could be derived from disequilibrium methods, and that the approach was of little value (see Laroque and Salanie 1995).…”
Section: On Theoretical Rigourmentioning
confidence: 99%
“…Historians have also underlined the discontinuities within these transformations, as well as the resistance against them (Goutsmedt, 2021;Goutsmedt et al, 2019;Renault, 2020), their varying impact on applied and empirical works (Boumans and Duarte, 2019;Qin, 2013;Renault, 2022), but also the existence of alternative theoretical research programmes (Backhouse and Boianovsky, 2013;Cherrier and Saïdi, 2018;Hoover, 2012). Nevertheless, these historical contributions remained generally US-centred.…”
Section: Introductionmentioning
confidence: 99%
“…For a presentation of new classical contributions in the 1970s, see De Vroey (2016); seeGoutsmedt et al (2019) for a more in-depth analysis of the context of the criticisms addressed to macroeconometric models.…”
mentioning
confidence: 99%